Lumbar Intervertebral Disc Degeneration Does Not Affect Muscle Synergy for Rowing Activities - Chie Sekine; Naoto Matsunaga; Yu Okubo; Mika Hangai; Koji Kaneoka (Applied Bionics and Biomechanics)
Rowers with disc degeneration may have motor control dysfunction during rowing. This study is aimed at clarifying the trunk and lower extremity muscle synergy during rowing and at comparing the muscle synergy between elite rowers with and without lumbar intervertebral disc degeneration. Twelve elite collegiate rowers (with disc degeneration, n=6; without disc degeneration, n=6) were included in this study. Midline sagittal images obtained by lumbar T2-weighted magnetic resonance imaging were used to evaluate disc degeneration. Participants with one or more degenerated discs were classified into the disc degeneration group. A 2000 m race trial using a rowing ergometer was conducted. Surface electrodes were attached to the right rectus abdominis, external oblique, internal oblique, latissimus dorsi, multifidus, erector spinae, rectus femoris, and biceps femoris. The activity of the muscles was measured during one stroke immediately after 20% and 80% of the rowing trial. Nonnegative matrix factorization was used to extract the muscle synergies from the electromyographic data. To compare the muscle synergies, a scalar product (SP) evaluating synergy coincidence was calculated, and the muscle synergies were considered identical at SP>75%. Both groups had only one module in the 20% and 80% time points of the trial. At the 20% time point of the 2000 m rowing trial, the SP of the module was 99.8%. At the 80% time point, the SP of the module was 99.9%. The SP results indicate that, at 20% and 80% time points, both groups had the same module. The module showed a high contribution in all muscles. The activation coefficients indicated that the module was always highly activated throughout the rowing stroke in both groups. The trunk and lower extremity muscles are mobilized through the rowing stroke and maintain coordination during rowing. There was no difference in the muscle synergy between the rowers with and without lumbar intervertebral disc degeneration.